The Quest for Improved Learning Outcomes in Literature-in-English among Senior Secondary School Students in Ibadan, Nigeria: Teachers’ Instructional Organisation in Focus (2022)
This study examined the relationship between teachers' instructional organisation and academic achievement of senior secondary school students in Literature-in-English in Ibadan, Nigeria using the survey design of the correlational type as the research design. The participants were 20 Literature-in-English teachers and 436 students in intact classes from 20 senior secondary schools in Ibadan. Instruments used were Achievement Test in Literature-in-English (r=0.78) and Teachers Instructional Organisation Scale (r-0.81). Two research questions were answered using descriptive statistics and Pearson Product Moment Correlation at 0.05'level of significance. Findings revealed that teachers’ instructional organisation was poor ( x = 2.62) against the threshold of 3.0; and that instructional organisation correlated positively with students' achievement in Literature-in-English. Consequent on these findings, it is recommended that teachers should attend professional development programmes such as seminars and workshops to improve their instruction organisation skill for improved learning outcomes of students